Ex-vivo assessment of drug response on breast cancer primary tissue with preserved microenvironments. (3rd July 2017) - Muraro, Manuele G.; Muenst, Simone; Mele, Valentina; Quagliata, Luca; Iezzi, Giandomenica; Tzankov, Alexandar; Weber, Walter P.; Spagnoli, Giulio C.; Soysal, Savas D.
ABSTRACT: Interaction between cancerous, non-transformed cells, and non-cellular components within the tumor microenvironment plays a key role in response to treatment. However, short-term culture or xenotransplantation of cancer specimens in immunodeficient animals results in dramatic modifications of the tumor microenvironment, thus preventing reliable assessment of compounds or biologicals of potential therapeutic relevance. We used a perfusion-based bioreactor developed for tissue engineering purposes to successfully maintain the tumor microenvironment of freshly excised breast cancer tissue obtained from 27 breast cancer patients and used this platform to test the therapeutic effect of antiestrogens as well as checkpoint-inhibitors on the cancer cells. Viability and functions of tumor and immune cells could be maintained for over 2 weeks in perfused bioreactors. Next generation sequencing authenticated cultured tissue specimens as closely matching the original clinical samples. Anti-estrogen treatment of cultured estrogen receptor positive breast cancer tissue as well as administration of pertuzumab to a Her2 positive breast cancer both had an anti-proliferative effect. Treatment with anti-programmed-death-Ligand (PD-L)-1 and anti-cytotoxic T lymphocyte-associated protein (CTLA)-4 antibodies lead to immune activation, evidenced by increased lymphocyte proliferation, increased expression of IFNγ, and decreased expression of IL10, accompanied by a massive cancer cell death in ex vivo triple negative breast cancer specimens. In the era of personalized medicine, the ex vivo culture of breast cancer tissue represents a promising approach for the pre-clinical evaluation of conventional and immune-mediated treatments and provides a platform for testing of innovative treatments.